Substituição da silagem de azevém pelo feno de alfafa na dieta de ovinos - Reffatti, Tiane Sueli (2018)
The objective of this study was to evaluate the effect of substitution of ryegrass silage (Lolium multiflorum L.) on alfalfa hay (Medicago sativa L.) on consumption, ruminal parameters and microbial protein synthesis in sheep. Four male, castrated, undefined, cannulated sheep in the rumen with a mean live weight of 50.0 kg were used in a 4x4 Latin square experimental design, with treatments being 15, 30 and 45% alfalfa hay and treatment only controls ryegrass silage. The experimental period was divided into four periods of 20 days, 15 for adaptation to diet and five for collection of feces, urine and ruminal fluid. Consumption of dry matter (DM) and digestible organic matter (MOD) showed a quadratic tendency for the inclusion levels of alfalfa hay. The pH value showed a quadratic trend among the different treatments, over time, with effect for all hours, with a maximum value of 7.26 and a minimum of 6.91 at 9 and 6 hours after feeding. The concentrations of sugars and amino acids changed over the hours, and the means of ammonia and inclusion levels influenced amino acids. The nitrogen (N) retained, digestible values ingested and the true digestibility of N showed significance for the inclusion levels and for N ingested and the efficiency of its N utilization a quadratic trend was found. Purine derivatives were not significant, the mean excretion of allantoin was 4.78 mmol day -1, mean uric acid excretion of 0.84 mmol day -1, the production of microbial protein was not influenced by the inclusion of levels of alfalfa hay. The inclusion of alfalfa hay increased the consumption of the animals up to the 30% level, presenting satisfactory results of microbial protein production and nitrogen efficiency.